(untitled) (Research, Society and Development, 2020)
Congenital Heart Disease presents itself as a variety of abnormalities in anatomy and/or cardiac function and can be classified as cyanotic or cyanotic. The treatment of this pathology is initially caused by the stabilization of symptoms, through oxygen supplementation and the administration of medications, such as alprostadil, in order to improve the quality of life of patients and prepare them for surgical correction. The aim of this study was to outline the profile of the use of alprostadil in neonatal patients with congenital heart disease. This is a descriptive, cross-sectional, retrospective study with quantitative approaches, carried out in a tertiary hospital in the public network of the State of Ceará. 79 medical records of patients from January 2015 to September 2019 who used alprostadil with or without diagnosis of congenital heart disease were evaluated. It was observed that the profile of neonates who used alprostadil was 12.7 days old, mean weight 2727.8g, classified appropriately regarding weight and gestational age. The prevalence of congenital heart disease was higher in males, brown skin and full-term newborns. The peripherally inserted catheter and induced mechanical ventilation were the most used forms of access and oxygenation. The echocardiogram was performed in 86% of newborns, reporting 78% of cyanogenic heart diseases. It is concluded that the use of alprostadil is safe and effective, however alone is not enough to increase the life days of neonatal patients with complex / multiple heart disease, given the severity of the changes.